Happiness in Europe: cross-country differences in the determinants of subjective well-being - Peder J. Pedersen; Torben Dall Schmidt (Institute for the Study of Labor (IZA), 2009)
The purpose in the present paper is to use individual panel data in the European Community Household Panel to analyse the impact on self-reported satisfaction from a number of economic and demographic variables. The paper contributes to the ongoing discussion of the relationship between life satisfaction and income. The panel property of the data makes it possible to study also the impact on satisfaction from income changes as well as the impact from acceleration in income and changes in labour market status on changes in satisfaction. A number of demographic variables and individual attitude indicators are also entered into the analysis of both the level of satisfaction and the change in satisfaction from one wave of the survey to the next. We find a strong impact from the level of income in all countries, an impact from change and acceleration in income for a smaller number of countries, a strong impact from most changes in labour market status and finally important effects from a number of demographic variables.
Keywords: C23; D31; I31; J28; 330; Satisfaction; income; labour market status; health; Lebenszufriedenheit; Einkommen; Erwerbsstatus; Gesundheit; Meinung; EU-Staaten